MODEL PENDUGA TRAFIK INTERNET BERDASARKAN PENDEKATAN FUZZY LOGIC (STUDI KASUS PT. SURYAMAS DUTAMAKMUR, TBK) - Martanto, Lilik (Aksara Public, 2018)
The development of Information and Communication Technology (ICT) that is so fast has an impact on changes in interaction that previously directly communicate to be virtual. Based on the similarity of interests and many preferences that make a particular community and then the online world is channeled by forming an Online Social Community Network in interacting in cyberspace. This provides an opportunity to do business development through Online Networks. This service improvement is certainly one of the ways for companies or organizations to emerge and to provide more services to customers especially internal companies. One form of service is the determination of Quality of Service or service quality. The calculated service quality is the average customer traffic value online. Fuzzy logic as part of artificial intelligence is able to make predictions about things. Compared to artificial neural networks that are able to make predictions and fuzzy logic is superior because there is no need for training data to determine output. By using fuzzy logic for the online customer traffic assessment model, it can be immediately known the value of the quality of Service. The valuation model used is using fuzzy logic. The input variables used are 3 variables and each variable has 3 membership sets. The output variable used is Quality of service, there are 3 sets in that variable which are whether under QOS, same as QOS, or above QOS